The Interwar Furniture in Lithuania: Design and History - Dičkalnytė, Aistė (Załącznik Kulturoznawczy, 2019)
This article analyses the furniture created in Lithuania during the interwar period. Today, from a time perspective, we can shed light on the development of furniture making, with the aim to reveal the furniture designers and the particular interiors where this kind of furniture became popular, as well as the styles that influenced them. In this paper, the author mostly describes artistic designs for secular interiors. The selection was based on the fact that this furniture best reflects the prevailing tendencies when it comes to design during a particular period. After independence was restored to Lithuania, the design of produced furniture became more modern and similar to that of Western Europe. This was caused by the educative propaganda in the media and the new generation of architects and artists who had graduated from universities in western countries. The new, rational construction of houses where all the free rooms were usually rented during the crisis caused demand of space-saving furniture. The architects usually designed both buildings and the built-in furniture with that concept in mind. Architects attempted to tailor built-in furniture to the user’s needs and financial capabilities in the most optimal way. Built-in modular storage systems, kitchen cupboards, and bookshelves were conceived as architectural components. They were used to divide and to model the space. The small living space required the number of furniture pieces to be reduced. That is why unit furniture became the second-most trending innovation during the interwar period. The combination of wardrobes, bookcases, and sideboards into one piece was the most popular modular unit furniture. Tables with shelves and couches with consoles were also popular examples of space-saving furniture. These modern innovations of furniture were made in art déco style since the late 1920s. The search for Lithuanian national style was particularly relevant in the interwar period and design was used as an instrument for political purpose. This is obviously prevalent in the furniture of representation interiors. Leading architects like Vytautas Landsbergis-Zemkalnis, Bronius Elsbergas, and Arnas Funkas, and also some popular artists such as Jonas Prapuolenis, Antanas Gudaitis, and Gerardas Bagdonavicius, designed not only furniture innovations but also furniture in the Lithuanian national style as part of their representative-interior projects. Country-wide Lithuanian exhibitions and presentations abroad were also dominated by the Lithuanian national style, propagated by the authorities. Interpretations of ethnic furniture decor and forms, as well as national symbols became dominant in all Lithuanian-national-style furniture.